Volatile and glycosidically bound composition of Loureiro and Alvarinho wines - Oliveira, J. M. (2008)
Composition of Loureiro and Alvarinho wines from the Vinhos Verdes region, respecting free volatile compounds as well as glycosidically bound aroma precursors, was exhaustively determined by GC-MS after adsorption on XAD-2 resin. On the whole, were identified and quantified 120 volatile compounds in the free fraction and 77 glycosidically bound compounds, belonging to C6-compounds, alcohols, fatty acids ethyl esters, esters of organic acids, acetates, monoterpenic alcohols, monoterpenic oxides and diols, C13-norisoprenoids, volatile phenols, volatile fatty acids and carbonyl compounds. Globally, the wines of the two cultivars present similar composition on volatiles. However, respecting varietal compounds, Loureiro wines are richer than Alvarinho ones with regard to C6-compounds and monoterpenic compounds, occurring the opposite for volatile phenols. It was also demonstrate that wines of both varieties may benefit the aroma reserve, present as glycoconjugates, as it is susceptible of being technologically explored. Linalool, Ho-trienol, α-terpineol, contributing with fruity and floral notes, and β-damascenone mostly for Alvarinho, confering tropical fruit notes, are the varietal compounds which may particularly influence the aroma of these wines. Respecting fermentative compounds, Alvarinho is also particularly rich in fatty acids ethyl esters related to lipid metabolism and acetates of fusel alcohols, which can provide it a fruity character; Loureiro contains higher levels of esters of organic acids and 2-phenylethanol, conferring fruity and floral notes. Sensory analysis agree with chemical analyses showing a pronounced tree and tropical fruit character for Alvarinho wines while Loureiro wines present more intense citrus fruit notes.